2018
DOI: 10.14744/semb.2018.55381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the knowledge of cow’s milk allergy in pediatricians

Abstract: Evaluation of the Knowledge of Cow's Milk Allergy among Pediatricians C ow's milk allergy (CMA) is one of the most common food allergies to occur in infants and children under 3 years of age. The incidence in early childhood varies between 2% and 7.5%. [1] Studies carried out in different regions in Turkey have recorded an incidence of between 0.55% and 1.55%. [2-4] Clinical symptoms of CMA manifest in infants fed with breast milk generally within the first months of life, and in infants fed with formula conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This study showed that regarding Cow Milk Symptoms Score among the studied group, 38.3% had knowledge of COMSS. This is in disagreement with Can et al (17) who evaluated Knowledge of Cow's Milk Allergy among Pediatricians. The results of their study indicated that occupational education significantly increased the level of knowledge about CMA in pediatricians.…”
Section: Discussionmentioning
confidence: 66%
“…This study showed that regarding Cow Milk Symptoms Score among the studied group, 38.3% had knowledge of COMSS. This is in disagreement with Can et al (17) who evaluated Knowledge of Cow's Milk Allergy among Pediatricians. The results of their study indicated that occupational education significantly increased the level of knowledge about CMA in pediatricians.…”
Section: Discussionmentioning
confidence: 66%
“… 17 A recent comparative study in Turkey reported that Training significantly raised the degree of CMPA knowledge among pediatric residents and practicing pediatricians. 18 …”
Section: Discussionmentioning
confidence: 99%
“…17 A recent comparative study in Turkey reported that Training significantly raised the degree of CMPA knowledge among pediatric residents and practicing pediatricians. 18 The International Pharmaceutical Federation (FIP) states that providing patients with the necessary knowledge for the best possible use of pharmaceuticals is the responsibility of pharmacists and that patient counseling is a top priority. 19 Community Pharmacists need to have a solid understanding of CMPA to provide effective counseling.…”
mentioning
confidence: 99%
“…LI is not life-threatening, but it does affect patients’ quality of life and well-being, and they may experience extreme discomfort caused by ineffective treatment [ 12 , 15 ]. Thus, medical students must recognize its diagnosis workup and management.…”
Section: Discussionmentioning
confidence: 99%